Polynomial regression models to explain the relationship between network and service key performance indicators. Issue 5 (1st September 2017) - Costantini, Luca; Mammi, Elena; Teodori, Marco; Attanasio, Vincenzo
Abstract : In the future networks, the level of quality of services (QoS) will be improved, new services will be introduced and the end users will enjoy everywhere and any time old and new services via fixed and mobile devices. Then the quality will be a key aspect for the next generation network. In this context, the relationship between the network performances and the QoS become an important issue. In this study, the quality of network and QoS in future system are studied, an agent to measure the key performance indicators values has been created and a polynomial regression models to explain the relationship between network and service KPIs is employed.